2003
DOI: 10.1046/j.1442-200x.2003.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiocirculatory effects of patent ductus arteriosus in extremely low‐birth‐weight infants with respiratory distress syndrome

Abstract: These results indicate that although LVO is increased, the splanchnic and renal blood flows are decreased when hsPDA develops in ELBW infants with RDS. The effects of these alterations of LVO and organ blood flows on the cardiorespiratory course seem to be minor when early pharmacologic closure of PDA is done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 28 publications
3
49
0
4
Order By: Relevance
“…Vanpée et al 26 showed that sick VLBW infants having a PDA and requiring mechanical ventilation had lower creatinine clearances and significantly higher fractional sodium excretion than controls; however, their study also included few infants who had received NSAID for ductus closure before evaluating renal function. Shimada et al 27,28 studied the cardiocirculatory effects of hsPDA in VLBW and extremely low BW preterm with RDS and they found a significant decrease in renal blood flow in infants with hsPDA compared to controls before pharmacological closure of Figure 1 Creatinine profile during the first week of life according to gestational age (GA) in 652 infants <32 weeks of GA. Creatinine changes in preterm infants S Iacobelli et al PDA. Abnormal renal blood flows reverted after treatment and seemed less severe when early pharmacological closure of PDA was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Vanpée et al 26 showed that sick VLBW infants having a PDA and requiring mechanical ventilation had lower creatinine clearances and significantly higher fractional sodium excretion than controls; however, their study also included few infants who had received NSAID for ductus closure before evaluating renal function. Shimada et al 27,28 studied the cardiocirculatory effects of hsPDA in VLBW and extremely low BW preterm with RDS and they found a significant decrease in renal blood flow in infants with hsPDA compared to controls before pharmacological closure of Figure 1 Creatinine profile during the first week of life according to gestational age (GA) in 652 infants <32 weeks of GA. Creatinine changes in preterm infants S Iacobelli et al PDA. Abnormal renal blood flows reverted after treatment and seemed less severe when early pharmacological closure of PDA was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Shimada et al 15 evaluated ascending aorta, celiac, superior mesenteric and renal artery blood flow by Doppler ultrasound in extremely low birth weight infants. They found that infants with a hemodynamically significant PDA had increased global left ventricular output, but decreased splanchnic blood flow compared with controls, and that these measures returned to normal following pharmacologic PDA closure with mefenamic acid.…”
Section: Introductionmentioning
confidence: 99%
“…PDA has been reported to be associated with morbidities in preterm infants as a result of ductal steal from systemic circulation, for example, pulmonary congestion, pulmonary hemorrhage, bronchopulmonary dysplasia, intraventricular hemorrhage and necrotizing enterocolitis. [1][2][3][4] Strategies for PDA closure involve prophylactic treatment, presymptomatic treatment for non-HsPDA, and treatment for HsPDA. 5,6 Although prophylactic treatment with indomethacin reduces incidence of PDA and severe intraventricular hemorrhage in preterm infants, 7,8 there are no differences in mortality and long-term neurodevelopment.…”
mentioning
confidence: 99%